2013
DOI: 10.3390/v5061414
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Naturally Occurring Simian Foamy Viruses (SFVs) on SIV Disease Progression in the Rhesus Macaque (Macaca mulatta) Model

Abstract: We have investigated the influence of naturally occurring simian foamy viruses (SFVs) on simian immunodeficiency virus (SIV) infection and disease in Indian rhesus macaques. Animals were divided into two groups based upon presence or absence of SFV; in each group, eight monkeys were injected with SIVmac239 virus obtained from a molecular clone and four were injected with medium. Blood was collected every two weeks for evaluation of SIV infection based upon T cell-subsets, plasma viral load, development and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Cases of HIV-1/SFV (17) or HTLV-1/SFV (unpublished data) coinfections have been found in humans. In macaques, experimental SIV infection in either non-SFV-infected or naturally SFV-infected animals revealed that SFV infection increases the pathology of SIV infection (18). Given the ongoing risk of exposure to these three primate retroviruses, especially in Central Africa, microbiological surveillance is required to better evaluate the potential clinical and physiopathological impact of such retroviral interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of HIV-1/SFV (17) or HTLV-1/SFV (unpublished data) coinfections have been found in humans. In macaques, experimental SIV infection in either non-SFV-infected or naturally SFV-infected animals revealed that SFV infection increases the pathology of SIV infection (18). Given the ongoing risk of exposure to these three primate retroviruses, especially in Central Africa, microbiological surveillance is required to better evaluate the potential clinical and physiopathological impact of such retroviral interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results underline the importance of extending current knowledge beyond the most studied prototype strain. Indeed, Tas interacts with promoters from host genes (Colas et al, 1995;Kido et al, 2002;Wagner et al, 2000;Wang et al, 2010), may be involved in clinically relevant interactions with lentiviruses (Choudhary et al, 2013), and is a potential (but still controversial) target of the immune system (Meiering and Linial, 2003;Regad et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…SFVs also merit study for their own potential impact on human health, as vectors for gene therapy and vaccination (Olszko and Trobridge, 2013), and because co-infection with other retroviruses has been reported in humans (Filippone et al, 2015;Switzer et al, 2008). Such a coinfection with SFV has deleterious consequences in macaques experimentally infected with SIV (Choudhary et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A single study reported histopathological findings in the kidney of FV-inoculated domestic cats indicative of syncytia formation [8]. In a more recent study conducted with simian immunodeficiency virus (SIV)-infected rhesus macaques, Choudhary and colleagues have shown that those coinfected with the simian FV (SFV) progressed faster to the acquired immune deficiency syndrome (AIDS), had higher SIV viral loads and accelerated CD4 + T-cell depletion when compared to animals singly infected with SIV [9]. This raises the possibility that FV can act as an opportunistic pathogen, modulating the pathogenic impact of other infections.…”
Section: Summary Of Scientific Sessionsmentioning
confidence: 99%